Polymorphism and Expression of HSD17Î²13 Gene and Its Association with Lamb Quality of Indonesian Sheep - Harahap, Ratna Sholatia; Noor, Ronny Rachman; Gunawan, Asep (ANIMAL PRODUCTION, 2021)
HSD17Î²13 (17beta 13-Hydroxysteroid dehydrogenases) are important enzymes in steroid metabolism. This study investigated the polymorphisms and expression of the HSD17Î²13 gene in lamb quality traits in Indonesian sheep. A total of 200 of rams of seven breeds administered in the study were Javanese fat-tailed (JFT), Javanese thin-tailed (JTT), Garut sheep (GS), Jonggol sheep (JS), Garut composite sheep (GCS), Compass agrinac sheep (CAS), Barbados cross sheep (BCS) aged 10-12 months and weighed 20-30 kg. The Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and MspI enzyme restriction were performed to identify the polymorphism of the HSD17Î²13 gene. The lamb quality traits were measured for physical quality, flavor, odor, and fatty acid composition. The results showed that the HSD17Î²13 gene was polymorphic and had three genotypes i.e., CC, CT, and TT. The highest genotype frequency was the CC when compared to the other genotypes. The allele frequency of HSD17Î²13 gene was not in Hardy Weinberg Equilibrium. The polymorphism of HSD17Î²13 gene was significantly (P<0.05) associated with the fatty acid composition and Saturated Fatty Acid (SFA), i.e., tridecanoic acid (C13:0), arachidic acid (C20:0), henecosanoic acid (C21:0), and tricosanoic acid (C23:0). The polymorphism was also significantly associated with the Monounsaturated Fatty Acid (MUFA) i.e. ginkgoleic acid (C17:1) and nervonoic acid (C24:1), and Polyunsaturated Fatty Acid (PUFA) i.e. eicosedienoic acid (C20:2). The level of expression of the HSD17Î²13 gene based on quantitative real time-PCR analysis results was not significantly different (P>0.05) among genotypes for lamb quality traits. It can be concluded that the polymorphism of HSD17Î²13 gene was associated with the fatty acid composition of lamb in Indonesian sheep.